2019
DOI: 10.3390/ijms20081879
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Tools in Regenerative and Translational Dentistry

Abstract: Human oral-derived stem cells can be easily obtained from several oral tissues, such as dental pulp, periodontal ligament, from gingiva, or periapical cysts. Due to their differentiation potential, oral-derived mesenchymal stem cells are promising for tissue engineering and regenerative medicine. The regenerative ability showed by some oral tissues strongly depends on their sleeping adult stem cell populations that are able to repair small defects and to manage local inflammation. To date, researchers are work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 64 publications
0
56
0
3
Order By: Relevance
“…Using q-PCR studies, the presence of transcripts was identified for genes associated with the neuronal phenotype, such as β-III tubulin, and for genes associated with the dopaminergic phenotype, such as tyrosine hydroxylase [58]. Gene expression and levels of protein production in hPCy-MSCs exposed to neurogenic culturing conditions showed a notable increase in neural markers [59].…”
Section: The Human Periapical Cyst-mesenchymal Stem Cells (Hpcy-mscs)mentioning
confidence: 99%
“…Using q-PCR studies, the presence of transcripts was identified for genes associated with the neuronal phenotype, such as β-III tubulin, and for genes associated with the dopaminergic phenotype, such as tyrosine hydroxylase [58]. Gene expression and levels of protein production in hPCy-MSCs exposed to neurogenic culturing conditions showed a notable increase in neural markers [59].…”
Section: The Human Periapical Cyst-mesenchymal Stem Cells (Hpcy-mscs)mentioning
confidence: 99%
“…Due to their excellent potential for multil-ineage differentiation, dental MSCs are considered as an ideal source for tissue engineering and regenerative dental medicine. To date, researchers are looking for a feasible, safe, and effective approach for regenerative and translational dentistry [ 16 ]. Three feasible regenerative strategies based on dental MSCs have been proposed to treat dental diseases in clinic ( Figure 2 ).…”
Section: Dental Msc-based Therapy For Dental Diseasesmentioning
confidence: 99%
“…Dental MSCs are regarded as ideal cells for dental tissue engineering since they possess a shared embryological origin with craniofacial tissue [ 94 ]. Biocompatible scaffolds provide a favorable 3D microenvironment for stem cells, which regulate proliferation and differentiation [ 16 ]. In regenerative dentistry, current dominating attempts and studies of scaffold-supported tissue engineering include regeneration of dentin, dental pulp, and periodontal tissue and formation of bioroot.…”
Section: Dental Msc-based Therapy For Dental Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using stem cells is now shifting to stem cell‐free concept by the administration of stem cell‐derived exosomes or conditioned media (Kusuma, Carthew, Lim, & Frith, ; Phinney & Pittenger, ). New approaches in scaffolds consist of additive manufacturing (3D printing), decellularizing and scaffold‐less strategies like self‐assembling, self‐organizing, and 3D bioprinting (Tatullo, Codispoti, Paduano, Nuzzolese, & Makeeva, ; Thomas et al, ). With great roles of growth factor in cell recruitment, proliferation, differentiation, and tissue repair, new strategic approaches to growth factors delivery are established (Mitchell, Briquez, Hubbell, & Cochran, ; Nyberg, Holmes, Witham, & Grayson, ).…”
Section: Introductionmentioning
confidence: 99%